Literature Review: Hubungan Biomekanika Lutut terhadap Faktor Risiko Pasien Osteoartritis Lulut - Khaeratul Washilah; Muhammad Siddik; Didik Dwi Sanyoto (Homeostasis, 2021)
Abstract: Osteoarthritis of the knee is a major cause of disability with age and this condition is expected to continue to increase rapidly in the future. In patients with osteoarthritis, the knee will show decreased functionality that can withstand joint pain, stiffness, and weakness of the limb muscles which will then lead to functional impairment. This objective is to analyze the relationship between knee biomechanics in patients with osteoarthritis of the knee and its risk factors, and to provide an overview of the appropriate punishment for cases of knee osteoarthritis. The results of this study indicate that there is a relationship between knee biomechanics and risk factors for knee osteoarthritis. Keywords: risk factors, osteoarthritis, biomechanics, kinesiology, and kinematics Abstrak: Osteoartritis lutut adalah penyebab kecacatan utama pada usia tua dan keadaan ini diperkirakan akan terus meningkat dengan pesat di masa yang akan datang. Pada pasien dengan osteoartritis lutut akan menunjukkan penurunan kapasitas fungsional yang dapat dikaitkan dengan nyeri sendi, kekakuan, dan hilangnya kekuatan otot-otot ekstremitas bawah yang nantinya akan menyebabkan gangguan fungsional. Tujuan penulisan ini adalah untuk menganalisis hubungan biomekanika lutut pasien osteoarthritis lutut dengan faktor risikonya, serta memberikan gambaran penalaksanaan yang tepat untuk kasus osteoarthritis lutut. Hasil dari penelitian ini menunjukkan terdapat hubungan antara biomekanika lutut dengan faktor risiko osteoarthritis lutut. Kata-kata kunci: faktor risiko, osteoartritis, biomekanika, kinesiologi, dan kinematika